Effects of reactant rotation on the dynamics of the OH + CH4 → H2O + CH3 reaction : a six-dimensional study - Song, Hongwei (2014)
The dynamics of the hydrogen abstraction reaction between methane and hydroxyl radical is investigated using an initial state selected time-dependent wave packet method within a six-dimensional model. The ab initio calibrated global potential energy surface of Espinosa-García and Corchado was used. Integral cross sections from several low-lying rotational states of both reactants have been obtained using the centrifugal sudden and J-shifting approximations. On the empirical potential energy surface, the rotational excitation of methane has little effect on the reaction cross section, but excited rotational states of OH inhibit the reactivity slightly. These results are rationalized with the newly proposed sudden vector projection model.